2013
DOI: 10.1128/jcm.00587-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Clostridium difficile Infection in a Major Chinese Hospital: an Underrecognized Problem in Asia?

Abstract: Clostridium difficile infection is almost unrecognized in mainland China. We have undertaken a study in a large Chinese teaching hospital in Changsha, Hunan, China, to identify cases of C. difficile, record patient characteristics, and define the molecular epidemiology with respect to ribotype distribution and cross-infection. Between April 2009 and February 2010, we examined fecal samples from 70 hospitalized patients with diarrhea who were receiving or had received antibiotics within the previous 6 weeks. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 29 publications
10
46
1
Order By: Relevance
“…The predominance of ribotype 017 strains in the set of isolates is similar to reports from healthcare centres in China (Hawkey et al, 2013;Huang et al, 2009), Taiwan (Chia et al, 2013), Korea (Shin et al, 2008) and Japan (Komatsu et al, 2003). There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The predominance of ribotype 017 strains in the set of isolates is similar to reports from healthcare centres in China (Hawkey et al, 2013;Huang et al, 2009), Taiwan (Chia et al, 2013), Korea (Shin et al, 2008) and Japan (Komatsu et al, 2003). There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001).…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, in line with other investigations reported, the current study yielded a 22.0 % incidence of C. difficile, compared with a 9.2 % incidence with the sole use of ImmunoCard for Toxin A and B (Cohen et al, 2010; Rajabally et al, 2013;Sloan et al, 2008;Terhes et al, 2009). The predominance of ribotype 017 strains in the set of isolates is similar to reports from healthcare centres in China (Hawkey et al, 2013;Huang et al, 2009), Taiwan (Chia et al, 2013, Korea (Shin et al, 2008) and Japan (Komatsu et al, 2003). There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001).…”
supporting
confidence: 66%
“…Yet, our previous study demonstrated significant genetic diversity in tcdA and tcdB, consistent with the results of toxinotyping based on the restriction fragment length polymorphism (RFLP)-PCR method (19,28). However, the simple classification of RFLP-PCR failed to explain more details about the epidemiological relevance and phylogenetic relationships between strains with different types of toxin genes, while the recently increased ST37 (RT017 [A Ϫ B ϩ ]) contribution (48%) for CDI cases and its epidemic potentiality in Asia (11,16) make it urgent to build a more finely described pattern to reveal the intrinsic epidemic characteristics. In the present study, we introduce a novel approach that is more discerning and accurate; for example, 13 ST35 and 11 ST2 strains were divided into 2 groups (A03B04 and A02B05 and A06B07 and A09B06, respectively).…”
Section: Discussionsupporting
confidence: 59%
“…Recently, a particular variant strain of C. difficile, ST37, which has been ribotyped as RT017 and produces toxin B only, has attracted increasing attention (11,12,16). This type of strain shows increased resistance to clindamycin and erythromycin, with concomitant greater risk to inpatient health (13,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation